Rancang Bangun Sistem Informasi Pengarsipan Surat Masuk Keluar Berbasis Website di Desa Gudang Tanjungsari - Kanda M. Ishak; Nova Indarayana Yusman; Arinda Nurmeilana (Ma'soem University, 2022)
Desa Gudang is located at Jalan Raya Tanjungsari No.365 Tanjungsari Sumedang 45362. The filing system currently running in Desa Gudang is still done manually and can only be done during working hours. Where the archiving process is the officer records incoming and outgoing mail data in a book and then stored in a filing cabinet that could be damaged or lost. Therefore, a new system is needed. The design of the Website-Based Information System for Archiving Incoming and Outgoing Mail is a system that will be built to facilitate the work of recording incoming and outgoing mail archives. The design method used in this information system in describing the data flow is by using OOAD (Object Oriented Analysis and Design) with the RUP (Rational Unified Process) model equipped with UML (Unified Modeling Language) development tools. Thus the design of the incoming and outgoing mail archiving information system that will be built can assist in the process of recording archives, and can overcome existing problems and archives can be accessed outside of working hours.